(untitled) (Journal of Parents and Teachers, 2024)
The article addresses the tensions in Spanish democracy related to the teaching of religion in the educational system. It discusses the regulation that allows the choice of content and teachers according to religion, as well as the discrepancies about its inclusion in the curriculum. In addition, the importance of facilitating the knowledge of cultural manifestations linked to religion without imposing restrictions in educational centers is emphasized.